Precision medicine, insulin-like growth factors and cancer therapy - Haim Werner; Ilan Bruchim (Exploration of Medicine)
Technological breakthroughs over the past quarter century have had a huge impact on the broad area of medicine. Biological processes are now amenable to integrative examination at multiple levels of analysis, ranging from molecular to organismal levels. The Human Genome Project, in particular, paved the way for a new age in medicine that is commonly referred to as Precision (or Personalized) Medicine. These changes in the health sciences world are perceived both from the patient and clinician’s perspectives. The present article focuses on the insulin-like growth factor-1 (IGF1) axis, an important endocrine network with key roles in physiological and pathological conditions. We aim to provide the reader with an overview of the basic and clinical aspects of the IGF system, with a particular emphasis on ongoing efforts to target the IGF axis for therapeutic purposes. The potential impact of precision medicine on IGF1 clinical research is discussed.